Spectral colour data (400-700nm) from Monte dei Corvi, near Ancona, Italy - Christian Zeeden; Frederik J Hilgen; Lucas Joost Lourens; Silja Hüsing (PANGAEA, 2013)
Orbital tuning and understanding climate response to astronomical forcing in the Miocene require detailed knowledge of the effect of tidal dissipation (Td) and dynamical ellipticity (dE) on astronomical solutions used to compute insolation and orbital target curves for paleoclimatic studies. These Earth parameters affect precession and obliquity; the determination of their effect is of fundamental importance, as phase relations between astronomical forcing and climate response can only be accurately calculated when the relative phasing between precession and obliquity is known. This determination can be achieved through comparison of solutions having different values for Td and/or dE with well-understood paleoclimate data. In this paper we use quantitative color records of precession-obliquity interference recorded in two successive 2.4 Myr eccentricity minima (9–9.6 and 11.5–12.10.167emMa) in the Monte dei Corvi section in northern Italy to constrain the effect of Td, using the assumption of a direct response of sapropels to insolation. This quantitative approach results in a minimum uncertainty of astronomically tuned age models of0.167em±0.167em0.8 kyr and Td values 0.95 and 1.05 for the 9–9.60.167emMa interval and of +4/-1 kyr (Td values between 0.95 and 1.15) for the 11.5–12.10.167emMa interval. This (un)certainty not only limits the precision of determining phase relations but also improves our understanding of the limitations of tuned time scales and determining phase relations in the Miocene.
Supplement to: Zeeden, Christian; Hilgen, Frederik J; Hüsing, Silja; Lourens, Lucas Joost (2014): The Miocene astronomical time scale 9-120.167emMa: New constraints on tidal dissipation and their implications for paleoclimatic investigations. Paleoceanography, 29(4), 296-307, https://doi.org/10.1002/2014PA002615